Resource Control and Estimation Based Fair Allocation (EBFA) in Heterogeneous Active Networks - Devi, K.V.; Thangaraj, C.; Mehata, K.M. (Informatica)
Resource Control and Estimation Based Fair Allocation (EBFA) in Heterogeneous Active Networks